ELABORAÇÃO, CONDIÇÕES DE SECAGEM E VIDA ÚTIL DE MASSAS ALIMENTÍCIAS ARTESANAIS - Silva, Lucas Martins da (2020)
Pasta is consumed worldwide, mainly due to its low cost, ease of transport, preparation and storage. For the analysis of the shelf life of foods, it is necessary to control several parameters. Thus, this work aimed to determine the effects of drying and t